Artificial Intelligence-Based Expert System for Recirculating Aquaculture Systems in Tulungagung Regency, East Java - Ani Dijah Rahajoe; Yushinta Aristina Sanjaya; Anna Fauziah; Rino Zakaria; Arif Setyo Wibowo (Plakat : Jurnal Pelayanan Kepada Masyarakat, 2025)
Freshwater fish farming in Indonesia plays a crucial role in supporting food security and the economy. UD Tirta Mas Agung Abadi, based in East Java, is a key player in the breeding and cultivation of freshwater ornamental fish, as well as providing feed and aquaculture equipment. The main challenge lies in the complexity of parameters in the recirculating aquaculture system (RAS), such as weather, water quality, temperature, pH, dissolved oxygen, and other chemical contents. The reliance on experts also makes it difficult for farmers to take quick and measured actions in aquaculture management. The first solution proposed is the development of an intelligent system application based on artificial intelligence (expert systems) to efficiently manage RAS parameters. Trials have shown that 95% of respondents found the application met their needs. The second solution involves enhancing the capacity of freshwater ornamental fish farmers through training and mentoring, with 90% of respondents successfully implementing new techniques at their farming locations. These innovations have the potential to improve the efficiency and sustainability of freshwater fish farming in Tulungagung Regency. Budidaya ikan air tawar di Indonesia memegang peranan penting dalam mendukung ketahanan pangan dan perekonomian. UD Tirta Mas Agung Abadi, yang berbasis di Jawa Timur, merupakan salah satu pelaku utama dalam pembenihan dan pembesaran ikan hias air tawar, serta menyediakan pakan dan peralatan budidaya. Permasalahan utama yang dihadapi adalah kompleksitas parameter dalam sistem akuakultur resirkulasi (RAS) seperti cuaca, kualitas air, suhu, pH, oksigen terlarut, dan kandungan kimia lainnya. Ketergantungan pada pakar juga menyulitkan petani untuk menentukan tindakan budidaya yang cepat dan terukur. Solusi pertama yang ditawarkan adalah pengembangan aplikasi sistem cerdas berbasis kecerdasan buatan (sistem pakar) untuk mendukung pengelolaan parameter RAS secara efisien. Uji coba menunjukkan 95% responden merasa aplikasi ini memenuhi kebutuhan mereka. Solusi kedua adalah peningkatan kapasitas petani ikan hias air tawar melalui pelatihan dan pendampingan, dengan hasil 90% responden berhasil mempraktikkan teknik baru di lokasi budidaya mereka. Inovasi ini berpotensi meningkatkan efisiensi dan keberlanjutan budidaya ikan air tawar di Kabupaten Tulungagung.